2018
DOI: 10.1002/pbc.27069
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis of appendiceal carcinoid tumors in children

Abstract: Appendicectomy alone is an adequate treatment for an appendicular carcinoid in children irrespective of size, position, lymph node, or mesenteric involvement. Post-appendicectomy investigations were found to be not helpful in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
36
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 38 publications
12
36
0
Order By: Relevance
“…Another issue is the high proportion of patients lost to FU or who opted out, as it happened in six patients of our series (23% of the total population). This was often reported in the past, 14,16,27 and in our experience it seems a consequence of parents’ decision to look for a second or third opinion in other centers outside the pediatric network.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Another issue is the high proportion of patients lost to FU or who opted out, as it happened in six patients of our series (23% of the total population). This was often reported in the past, 14,16,27 and in our experience it seems a consequence of parents’ decision to look for a second or third opinion in other centers outside the pediatric network.…”
Section: Discussionsupporting
confidence: 50%
“…Bronchi and pancreas seem to represent the most frequent sites in extra‐appendicular NET, 3,14 but it is undoubted that the true incidence remains currently unveiled. A report from the Surveillance, Epidemiology, and End Results (SEER) registry demonstrated that in children the bronchial NETs occurred more frequently than the appendicular tumors, 3 but the number of appendicular NET might be underestimated due to their benign course 1,16–18 . Moreover, series from single institution, though covering a long frame of time, seem to alternately over‐ or underestimate the site of occurrence 15,19,20 .…”
Section: Discussionmentioning
confidence: 99%
“…For tumors of this size, previous studies have indicated that appendectomy is sufficient. The guidelines set by The North American Neuroendocrine Society (NANETS) reveal that right hemicolectomy is recommended for tumors originating at the base of the appendix, tumors >2 cm in size, if there is evidence of lymphovascular or meso-appendiceal invasion, in patients with lymph node metastases, or for intermediate or high-grade tumors [22,23]. In regards to those tumors between 1 cm and 2 cm, there is no clear consensus.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of pediatric carcinoid tumors found that in 91% cases, carcinoid was only identified following histology, as we report in our case. 5 The majority of studies in this review report cases of appendectomies undertaken for symptomatology, acute appendicitis or chronic abdominal pain with a carcinoid incidence of 0.3% of appendectomies. 5 Incidental appendectomies, performed in an adult population of patients with normal appendices, demonstrated a much higher carcinoid incidence of 1.6%.…”
Section: Discussionmentioning
confidence: 99%